Potential tunable white-emitting phosphor lt;LiSr4(BO3)3:Ce3+, Eu2+ for ultraviolet light-emitting diodes - Wang, Q.; Deng, D.; Hua, Y.; Huang, L.; Wang, H.; Zhao, S.; Jia, Guohua; Li, C.; Xu, S. (2012)
A novel Ce3/Eu2 co-activated LiSr4(BO 3)3 phosphor has been synthesized by traditional solid-state reaction. The samples could display varied color emission from blue towards white and ultimately to yellow under the excitation of ultraviolet (UV) light with the appropriate adjustment of the relative proportion of Ce 3/Eu2. The resonance-type energy transfer mechanism from Ce3 to Eu2 in LiSr4(BO3) 3:Ce3, Eu2 phosphors is dominant by electric dipoledipole interaction, and the critical distance is calculated to be about 29.14 Å by the spectra overlap method. White light was observed from LiSr4(BO3)3:mCe3, nEu2 phosphors with chromaticity coordinates (0.34, 0.30) upon 350 nm excitation. The LiSr4(BO3)3:Ce3, Eu2 phosphor has potential applications as an UV radiation-converting phosphor for white light-emitting diodes. © 2011 Elsevier B.V. All rights reserved.